Peer tutoring: its effects on subject mastery and Mathematics anxiety among elementary education teaching interns - M Petancio, Jo Ann; B Perez, Noremay; N Javier, Nigel Glenn (Penerbit Universiti Kebangsaan Malaysia, 2020)
Teachers’ subject mastery and anxiety towards mathematics affect their performance in teaching the subject. This quasi-experimental study aimed to determine the effects of peer tutoring on mathematics subject mastery and mathematics anxiety among teaching interns. Intact groups of 35 Bachelor of Elementary Education (BEEd) students participated as tutees and 32 Bachelor of Secondary Education (BSEd) students with specialization in Mathematics participated as tutors in this study. Quantitative data were analysed using inferential statistics. Results revealed that peer tutoring was effective in increasing mathematics subject mastery; however, it had not been effective in reducing mathematics anxiety. Moreover, albeit insignificantly, as the participants’ subject mastery increases, their anxiety decreases, and that mathematics anxiety is an insignificant predictor of subject mastery. The findings implicate that a peer tutoring program can be beneficial in equipping general education prospective teachers with sufficient content knowledge and confidence to teach mathematics; hence, further research on a functional peer tutoring process is recommended. Moreover, it is also suggested that future research be conducted on peer tutoring for other subject areas and prolonged period of peer tutoring sessions.